Mu’tazilah : Sejarah Rasionalisme Islam, Dinamika Kekuasaan Abbasiyah, dan Relevansinya dalam Pemikiran Kontemporer - Yoga Adhitya Fredy Firmansyah; Livie Izzati Hasanah; Muhammad Muzzammil Akbar (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2026)
Mu'tazilah is an ancient Islamic theological school of thought that has had a significant influence on the growth of rational and scholarly Islamic thought. This paper aims to examine the historical journey of Mu'tazilah since its emergence after the Tahkim incident following the Battle of Siffin. It explores the dynamics of cross-debate that accompanied it and its contribution to the advancement of science during the Abbasid dynasty, especially during the reigns of Caliphs al-Ma'mun and al-Mu'tasim. Using a descriptive historical approach and conceptual analysis, this study proves that the main concepts of Mu'tazilah, such as al manzilah bayna al manzilatayn and the focus on rationality, not only sparked theological debates but also stimulated the modernization of academic traditions through translation movements and the solidification of educational institutions such as Bait al Hikmah. Although the authoritarian implementation of Mu'tazilah teachings through mihnah regulations led to public resistance and contributed to its downfall, the intellectual legacy of Mu'tazilah is still relevant in the contemporary context. The rational ideas of Mu'tazilah are embodied in the concept of modern Islamic reform, including the views of Harun Nasution in Indonesia and the works of theological figures such as al Jahiz, who made significant contributions to the disciplines of linguistics and sociology. This study confirms that the rational and critical methods of Mu'tazilah still have important value in the development of Islamic theology that is interactive, adaptive, and sensitive to the challenges of the modern era.